2021
DOI: 10.3390/nu13020369
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition According to GLIM Criteria Is Associated with Mortality and Hospitalizations in Rehabilitation Patients with Stable Chronic Obstructive Pulmonary Disease

Abstract: Malnutrition has a negative impact on patients with chronic pulmonary obstructive disease (COPD). The purpose of this study was to assess the prevalence of malnutrition, defined by the Global Leadership Initiative for Malnutrition (GLIM), in stable COPD patients referred to pulmonary rehabilitation, and to explore potential associations of malnutrition according to GLIM, and its components, with increased risk of mortality and hospitalizations in 2 years. In a post-hoc analysis of a prospective cohort of 200 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 37 publications
0
53
0
Order By: Relevance
“…10 Malnutrition according to GLIM criteria was associated with mortality, survival prediction, and clinical outcomes in patients with cancer, chronic obstructive pulmonary disease, and heart failure. [11][12][13][14] Several studies have shown positive results using phase angle (PhA) as a nutrition and prognostic marker for malnutrition. 15,16 PhA is a raw indicator of the cell membrane integrity and functionality.…”
Section: Introductionmentioning
confidence: 99%
“…10 Malnutrition according to GLIM criteria was associated with mortality, survival prediction, and clinical outcomes in patients with cancer, chronic obstructive pulmonary disease, and heart failure. [11][12][13][14] Several studies have shown positive results using phase angle (PhA) as a nutrition and prognostic marker for malnutrition. 15,16 PhA is a raw indicator of the cell membrane integrity and functionality.…”
Section: Introductionmentioning
confidence: 99%
“…Both malnutrition and sarcopenia are common in patients with COPD. Malnutrition may affect about 50% of elderly individuals with COPD [ 17 ], and sarcopenia may be present in one in four to one out of seven patients, particularly those with severe and very severe obstruction [ 18 , 19 , 20 , 21 ]. Catabolic processes are intensified both in COPD and aging, leading to the reduction of muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…We found four studies assessing the prevalence of sarcopenia diagnosed based on the EWGSOP2 criteria in patients with COPD, including two papers concerning elderly subjects [ 18 , 19 , 20 , 21 ].Tsekoura et al [ 18 ] analyzed a group of 69 elderly patients with COPD (mean age 71.33 ± 7.48 years). They diagnosed sarcopenia in 17 participants (24.6%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations